2016
DOI: 10.1002/ange.201600603
|View full text |Cite
|
Sign up to set email alerts
|

A Symmetric Recognition Motif between Vicinal Diols: The Fourfold Grip in Ethylene Glycol Dimer

Abstract: Ethylene glycol has atransiently chiral, asymmetric global minimum structure,b ut it favors ah ighly symmetric, achiral dimer arrangement which has not been considered or found in previous quantum-chemical studies.C omplementary FTIR and Raman spectroscopyinsupersonic jets allows for the detection and straightforwarda ssignment of this four-fold hydrogen-bonded dimer,w hich introduces an interesting supramolecular binding motif for vicinal diols and provides astrong case for transient chirality synchronization… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 52 publications
0
1
0
Order By: Relevance
“…The Caf+Phenol [15] study demonstrated that many standard computational methods are not accurate in modelling complexes and/or vibrational frequencies, in which the final shapes are determined by a subtle balance between several weak interactions. In this study, we used two computational methods to test the validity of the computational predictions: a Minnesota functional [19], which has proven to be appropriate for the description of sugars (M06-2X/6-311++G(d,p)) [20][21][22][23], along with Grimme's dispersioncorrected B3LYP functional (B3LYP-GD3BJ) coupled to the def2TZVP basis set, which has recently demonstrated to produce accurate predictions for the spectra recorded in jets [24][25][26][27].…”
Section: Exploration Of the Intermolecular Potential Energy Surface (...mentioning
confidence: 99%
“…The Caf+Phenol [15] study demonstrated that many standard computational methods are not accurate in modelling complexes and/or vibrational frequencies, in which the final shapes are determined by a subtle balance between several weak interactions. In this study, we used two computational methods to test the validity of the computational predictions: a Minnesota functional [19], which has proven to be appropriate for the description of sugars (M06-2X/6-311++G(d,p)) [20][21][22][23], along with Grimme's dispersioncorrected B3LYP functional (B3LYP-GD3BJ) coupled to the def2TZVP basis set, which has recently demonstrated to produce accurate predictions for the spectra recorded in jets [24][25][26][27].…”
Section: Exploration Of the Intermolecular Potential Energy Surface (...mentioning
confidence: 99%